Giving Desert Its Due - Sadurski, Wojciech. author. aut Link
XII, 329 p.
Keywords: During the last half of the twentieth century, legal philosophy (or legal theory or jurisprudence) has grown significantly. It is no longer the domain of a few isolated scholars in law and philosophy. Hundreds of scholars from diverse fields attend international meetings on the subject. In some universities, large lecture courses of five hundred students or more study it. The primary aim of the Law and Philosophy Library is to present some of the best original work on legal philosophy from both the Anglo-American and European traditions. Not only does it help make some of the best work avail able to an international audience, but it also encourages increased awareness of, and interaction between, the two major traditions. The primary focus is on full-length scholarly monographs, although some edited volumes of original papers are also included. The Library editors are assisted by an Editorial Advisory Board of internationally renowed scholars. Legal philosophy should not be considered a narrowly circumscribed field.